The Use of e-Learning Platform by Primary School Teachers in West Sumatera - Meylina, Meylina (International Journal Of Pedagogical Novelty (IJOPNOV), 2022)
Since Indonesia declared the COVID19 pandemic emergency, all elementary schools have implemented an online learning system. However, in January 2021, the Padang City Government decided to introduce a private learning system with rules that comply with health protocols.Nevertheless, the problem of e-readiness was identified as the main challenge that influences teachers to become good facilitators for online learning. The purpose of this study is to find out how elementary school teachers in West Sumatra try to incorporate e-learning into their classrooms and what factors influence their motivation. The approach used in this study is a qualitative approach by distributing questionnaires to 30 respondents. Analytical interactive model was used to analyze the data and it was found that teachers in schools located in city centers with adequate internet access were ready to implement e-learning systems. There are also significant differences in motivation levels between public and private school teachers. In addition, several factors have been identified that teachers should consider supporting their desire to learn online including those related to well-instruction, high-quality content, good relationships, and good mental health.